Organic production in protected areas of the upper Danube region - Marijana Jovanović; Bojana Bekić; Lana Nastić (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Organic production requires strictly controlled conditions for the implementation on specific locality. Fulfillment of conditions of reduced use of chemicals, the use of unpolluted water, creating a protective belt around the farms and fields, preventing pollution, we get the basis for the development of this method of production with environmental protection and good quality of final products. Organic products have a major role in the strengthening of the local environment; it provides certified production provides a stable economic niche to sell in the domestic and foreign markets. The advantages of the area of the Upper Danube region lies in the fact that the spreads in the part of Serbia known for intensive organic agriculture in the AP Vojvodina. This paper will present recent results in organic production in the Republic of Serbia, with emphasis on the territory of the Upper Danube, as well as opportunities for future development of organic farming in the territory of the protected area of the Upper Danube municipal administration. Closeness of the Danube River opens new possibilities for connecting local markets.
Keywords: 330; organic production; local environment; Upper Danube region